Aproveitamento dos resíduos da cadeia produtiva do frango de Corte: compostagem, obtenção de chás de composto e uso dos Compostos como substratos para produção de muda - Lorin, Higor Eisten Francisconi (2019)
In recent years, Brazil has been one of the largest producers and exporters of broiler meat in the world and organic waste management is one the innumerable actions of this activity. This study presents the composting process as a method for recycling the main wastes of poultry production chain (PPC). Recycling these wastes is aligned with the principles of circular economy and shows the fertilizer potential of the organic compost and its different uses, both in liquid and in substrate form for the seedlings production. Five formulations of PPC mixtures wastes with five distinct bulking agents (BA) were stabilized by composting process. The factorial analysis of the evolution process indicates two main factors: (i) stabilization, related to the mineralization of organic matter (OM) and the phytotoxicity reduction; (ii) maturation, linked to humification and polymerization of the remaining OM in the composts. The improvements obtained due to the maturation stage, with 15 days are the same as with 80 days. This allows the reduction and optimization of the time of this phase. Water infusions of composted organic materials are called compost tea. Twenty compost teas were obtained from composts produced in the composting process. The focus was on the effect of the composting phases of macronutrients extraction (N, P and K) and the chemical, physicochemical and biological characteristics of the compost teas obtained. K is the most extractable macronutrient in compost teas, with higher percentages (30-70%) of N (2-12%) and of P (1-7%). The increase in electrical conductivity (EC) in compost teas decreases linearly the germination index (GI). EC values greater than 4.7 dS.m-1 suppress the phyto-stimulant effect (GI > 101%) of the compost teas, whereas EC ≥ 8.1 dS.m-1 shows phytotoxicity (GI < 66%). In order to use the agro-industrial composts as substrate for the production of vegetable seedlings it is necessary to adapt their physicochemical characteristics. For this, the addition of remaining charcoal from furnaces (RCF), another PPC waste, to the composts was investigated. The addition of RCF reduces the EC of the elaborated substrates. Through regressions, it was found that in order to achieve the highest seedling quality indexes and the most efficient soil clod removal from tray, it is necessary to add 30%, in weight, of RCF in composts using BA from urban tree pruning, sawdust and sugar cane bagasse. The BA of cotton residue and Napier grass, used in the PPC wastes, make it unfeasible to use as a substrate for the production of lettuce seedlings due to high EC.